2020
DOI: 10.1111/jav.02487
|View full text |Cite
|
Sign up to set email alerts
|

Central place foraging in a human‐dominated landscape: how do common cranes select feeding sites?

Abstract: Human infrastructure and disturbance play an important role when animals select resources in human‐modified landscapes. Theory predicts that animals trade food intake against costs of movement or disturbance to optimize net energy gain and fitness, but other necessary resources may also constrain the decisions, e.g. when animals repeatedly need to return to a central location, such as a nest, waterhole or night roost. Central place foraging theory states that the probability of occurrence of an animal decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Cranes may increasingly depend upon agricultural fields around Poyang Lake, which may, in turn, cause significant crop damage and economic losses. This is especially true on agricultural fields surrounding protected wetlands where waterbirds concentrate in high numbers [ 116 , 117 ]. At Poyang Lake, cranes mainly fed on post-harvest remains of rice seeds and lotus rhizomes; thus, crop damage and economic loss were limited.…”
Section: Discussionmentioning
confidence: 99%
“…Cranes may increasingly depend upon agricultural fields around Poyang Lake, which may, in turn, cause significant crop damage and economic losses. This is especially true on agricultural fields surrounding protected wetlands where waterbirds concentrate in high numbers [ 116 , 117 ]. At Poyang Lake, cranes mainly fed on post-harvest remains of rice seeds and lotus rhizomes; thus, crop damage and economic loss were limited.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was, however, limited to the growing season and to one diversionary field, consequently we could not analyse additional factors known to influence the use and selection of the landscape and consequent variation in damage risk to arable land (e.g. seasonality, distance to roost site, disturbance, agricultural practices, crop nutrient content; Nilsson et al., 2016, 2020; Fox et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, additional landscape characteristics (e.g. distance to forest edge, roads, settlements) may affect field selection by large grazing birds and should thus also be considered to maximise use of birds of diversionary fields (Jensen et al., 2017; Nilsson et al., 2020). Knowledge about how large grazing birds respond to the combined strategy of scaring and diversionary fields is limited, but it has been shown that low refuge availability reduced the effectiveness of diversionary feeding and scaring, and that diversionary feeding may cause habitat shift and reduction in activity areas for common cranes (Pekarsky et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, movement is affected by three components: potential energy gain of foraging, energetic losses through movement (and foraging) itself, and potential energy loss through predation risk avoidance. To both maximize gain and minimize risk, the forager could forage closer to its shelter or refuge (i.e., safe place to rest), as described in the central‐place foraging theory (foragers first exploit patches near the central location, except if distant patches have high quality and profitable resources; Bakker et al, 2005; Fryxell, 1999, Nilsson et al, 2020; Orians & Pearson, 1979; Schoener, 1979).…”
Section: Introductionmentioning
confidence: 99%